2012
DOI: 10.1002/bsl.2004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of ADHD and Its Subtypes in Male and Female Adult Prison Inmates

Abstract: There are few published studies of attention-deficit/hyperactivity disorder (ADHD) in adult inmates, and even fewer studies that have considered ADHD in adult inmates by gender. The present study examined the prevalence of ADHD, its subtypes, and associated psychological and neuropsychological comorbidity as a function of gender in a sample of 3,962 inmates (3,439 men and 523 women; mean age = 33.6 years, range 17-73) who had completed the 250-item, self-report, Diagnostic and Statistical Manual of Mental Diso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 33 publications
(39 reference statements)
1
40
0
1
Order By: Relevance
“…These rates are largely consistent with the childhood community prevalence estimates of approximately 4.2% in boys and 1.8% in girls (Cuffe, Moore, & McKeown, 2005). Deviations from this pattern occur most often in samples at risk for other psychological difficulties (e.g., Cahill et al, 2012;de los Cobos et al, 2011). The generally higher rate of ADHD in males compared to females across childhood into adulthood is, however, not universally present, as one-third of the studies found increased prevalence in women (see Table 1).…”
Section: Prevalencesupporting
confidence: 73%
“…These rates are largely consistent with the childhood community prevalence estimates of approximately 4.2% in boys and 1.8% in girls (Cuffe, Moore, & McKeown, 2005). Deviations from this pattern occur most often in samples at risk for other psychological difficulties (e.g., Cahill et al, 2012;de los Cobos et al, 2011). The generally higher rate of ADHD in males compared to females across childhood into adulthood is, however, not universally present, as one-third of the studies found increased prevalence in women (see Table 1).…”
Section: Prevalencesupporting
confidence: 73%
“…This variability could be due to differences in measurement; some studies have employed a self-report screening tool as in the current study (e.g. Edvinsson et al 2010;Hennessey et al 2010;Cahill et al 2012), with variation in the tools used, whilst others have utilised diagnostic interview schedules (e.g. Gunter et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In a large sample of men and women prisoners, Cahill et al (2012) reported an overall prevalence of ADHD of 10.5%, with more females (15.1%) reporting symptoms on a Diagnostic and Statistical Manual of mental disorders-5 th edition (DSM-IV; APA 1994) aligned self-report questionnaire than males (9.8%). Gunter et al (2008) reported similar rates of ADHD following clinical diagnostic interviews with male and female prisoners; 14.3% of women met criteria for lifetime and current ADHD.…”
Section: Prevalence Of Adult Adhd In An All Female Prison Unitmentioning
confidence: 99%
See 1 more Smart Citation
“…Des études de cohorte de naissances ont également montré que le TDAH était lié à une trajectoire de comportements agressifs qui persistait de l'enfance à l'âge adulte (Odgers et al, 2007) et à un risque plus élevé de décès par suicide à l'âge adulte (Barbaresi et al, 2013). Dans les milieux carcéraux, la prévalence du TDAH se situe générale-ment autour de 10 à 20 % (Cahill et al, 2012 ;Colins et al, 2010 ;Fazel, Doll et Langstrom, 2008 ;Retz et Rösler, 2010 ;Usher, Stewart et Wilton, 2013 ;Westmoreland et al, 2010), mais des taux plus élevés ont aussi été rapportés (Einarsson, Sigurdsson, Gudjonsson, Newton et Bragason, 2009 ;Ginsberg, Hirvikoski et Lindefors, 2010 ;Rösler et al, 2004). Plusieurs études démontrent que le TDAH se présente le plus souvent en comorbidité avec d'autres troubles, en particulier les troubles de l'humeur, les troubles anxieux, les troubles psychotiques, le trouble de la personnalité limite, le trouble de la personnalité antisociale et les troubles liés à l'utilisation de substances (alcool et drogue) (Einarsson et al, 2009 ;Rösler et al, 2004 ;Spencer et al, 2007 ;Westmoreland et al, 2010).…”
Section: Mots Clés • Prison Tentative De Suicide Tdah Santé Mentaleunclassified